Phylogenetic Analysis and Structural Modeling of SARS-CoV-2 Spike Protein Reveals an Evolutionary Distinct and Proteolytically Sensitive Activation Loop - Jaimes, Javier A. (J Mol Biol, 2020)
The 2019 novel coronavirus (2019-nCoV/SARS-CoV-2) originally arose as part of a major outbreak of respiratory disease centered on Hubei province, China. It is now a global pandemic and is a major public health concern. Taxonomically, SARS-CoV-2 was shown to be a Betacoronavirus (lineage B) closely related to SARS-CoV and SARS-related bat coronaviruses, and it has been reported to share a common receptor with SARS-CoV (ACE-2). Subsequently, betacoronaviruses from pangolins were identified as close relatives to SARS-CoV-2. Here, we perform structural modeling of the SARS-CoV-2 spike glycoprotein. Our data provide support for the similar receptor utilization between SARS-CoV-2 and SARS-CoV, despite a relatively low amino acid similarity in the receptor binding module. Compared to SARS-CoV and all other coronaviruses in Betacoronavirus lineage B, we identify an extended structural loop containing basic amino acids at the interface of the receptor binding (S1) and fusion (S2) domains. We suggest this loop confers fusion activation and entry properties more in line with betacoronaviruses in lineages A and C, and be a key component in the evolution of SARS-CoV-2 with this structural loop affecting virus stability and transmission.